Rationalized realities : an interpretation of the narrated lived experiences of African international student migrants staying in Finland - Ndomo, Quivine (2018)
The purpose of the thesis is to find out the migrant rationality of international African migrants who make the decision of staying in Finland. The purpose is to examine these migrant’s specific framework of reasons, logic, practices and motivations. The point of view of the thesis is that theories of international migration are limited by the structure agency disunion in the social sciences. Further, the migration phenomenon is perceived as complex, dynamic and diverse thus requiring alternative approaches. This thesis applies the social constructionist approach to examine the stance of actor agency in the context of migration. The method of analysis is the data driven technique developed from Corbin and Strauss’s techniques and procedures of qualitative data analysis. The data of the thesis is composed of transcribed interview audio recordings of 20 International migrants from Gambia, Ghana, Kenya, Nigeria and Zambia. The data is a collection of detailed migrant accounts shared by migrants during individual semi structured in-depth interviews. My research results suggest that migration is a time and a domain specific process that undergoes key transformation over its time span. In light of my data, it can be argued that the migration trajectory of these group of migrants is influenced by a configuration of constraints emanating from the structure, and the migrants’ agency freedom. Individual transformation is pursued and achieved collectively within migrant networks. Based on the research results, it can be concluded that African migrants in Finland collectively engage in the development and acquisition of a migrant habitus that directs their migration trajectory towards perceived success.